LEGITIMASI DATA PEMETAAN DIGITAL BERBASIS ARTIFICIAL INTELLIGENCE SEBAGAI ALAT BUKTI HAK ATAS TANAH (TANTANGAN HUKUM DI LUAR KERANGKA REGULASI KONVENSIONAL) - Geta Ilham Adi Prasetyo; Desi Sukmawati; Ahmad Fahmi Yustirandi; Budi Salman Farizy; Ajie Sefi Al Carubani (Jurnal Pertanahan, 2026)
The development of Artificial Intelligence (AI)-based digital mapping technology has brought significant changes to land administration practices and the resolution of land rights disputes. However, the use of AI-based digital mapping data as legal evidence has not yet gained clear normative recognition in Indonesia's land law system. This study aims to analyse the legal position of AI-based digital mapping data in the land law evidence system, identify normative gaps in its regulation, and formulate a legal regulatory model that can provide legitimacy and legal certainty for the use of AI technology as evidence of land rights. This study uses a normative juridical research method with a legislative approach, a conceptual approach, and a case approach. The legal materials used include primary, secondary, and tertiary legal materials that are analysed qualitatively. The results of the study show that although electronic documents have been recognised as legal evidence, the regulations do not specifically accommodate the characteristics of AI-based digital mapping data, which is dynamic, algorithm-based, and non-physical. This condition creates a normative gap that has implications for legal uncertainty in proving land rights. This study concludes that legal reform is needed through the formulation of specific norms governing the legitimacy, validity standards, verification mechanisms, and auditability of AI-based digital mapping data to ensure legal certainty, protection of land rights, and adaptation of land law to developments in digital technology. Keywords: Digital Mapping, Artificial Intelligence, Evidence, Land Law, Legal Certainty.